An Industrial Add-On for Precision Die-Centering in Catheter Extrusion Using Visual Servoing - Han Chang Lee; Byeong Hak Kim; Jong Pil Yun; Gyu Man Kim; Woojin Kim; Hong-In Won (IEEE Access)
This paper presents a real-time visual servoing system for automating die-centering in catheter extrusion processes. By leveraging state-of-the-art image processing algorithms, the system dynamically adjusts the positions of the extrusion head and tip in real time, ensuring precise alignment and significantly enhancing product consistency and quality. The proposed algorithm, a cornerstone of intelligent manufacturing, has been rigorously tested under diverse extrusion head types and operational conditions, demonstrating robust performance and precise detection of the die’s inner circle and the tip’s center position. In particular, the developed algorithm achieved a mean IoU (Intersection over Union) of 0.95, demonstrating exceptional robustness in inference performance even under dynamic conditions, such as the positional movements of the add-on system. The control signals generated by the algorithm were employed to align the tip and die, achieving precise operations at a scale of tens of micrometers, thereby validating the system’s high accuracy and reliability. Designed for seamless integration into existing manufacturing environments, the system requires minimal modifications, making it highly adaptable. By addressing long-standing challenges in die-centering operations, this intelligent manufacturing innovation not only increases production efficiency but also elevates product reliability.